2018
DOI: 10.1111/ijfs.13861
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of gluten and gluten‐starch model doughs containing wheat bran dietary fibre

Abstract: Summary The effect of wheat bran dietary fibre (WBDF) on the texture and extensional properties of gluten (G) as well as gluten‐starch (G+S) doughs were investigated. Texture analysis revealed an increasing hardness of WBDF‐enriched doughs, ascribed to the gradual formation of intermolecular hydrogen bonds and weakened aggregation behaviour of gluten proteins. Extension results showed that G and G+S systems exhibited growing extension resistance thanks to the strengthened strain‐hardening capacity induced by W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 32 publications
1
25
0
1
Order By: Relevance
“…The experimental results were expressed as the ratio of the corresponding area to the total amide I band area (percentage) and are summarised in Table , which quantify the changes in these secondary structures. The repeated β‐turn structures are reported to form a helix, which can be extended to 130% of its original length (Han et al , ). In other words, the decrease of the turn leads to an increase in helix.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental results were expressed as the ratio of the corresponding area to the total amide I band area (percentage) and are summarised in Table , which quantify the changes in these secondary structures. The repeated β‐turn structures are reported to form a helix, which can be extended to 130% of its original length (Han et al , ). In other words, the decrease of the turn leads to an increase in helix.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of WBDF was conducted according to our earlier study . Briefly, wheat bran was ground and washed using a colloid mill to remove the starch and soluble fractions.…”
Section: Methodsmentioning
confidence: 99%
“…However, numerous studies have demonstrated the unfavorable viscoelasticity of wheat bran‐fortified wheat flour products with regard to the rough crumb, small volume and hard texture that is responsible for the limited consumption of whole grain products . We recently found that wheat bran dietary fiber (WBDF) adversely affected the springiness and extensibility of doughs and produced a more rigid and harder dough texture . Accordingly, to address the consumption problem of whole grain products, the adverse effects of WBDF on dough viscoelasticity should be more thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantage of the gluten‐free flours in pasta making is that they cannot create a sufficiently strong network between their protein and starch to bind the dough and produce the required quality (Djordjević et al, ; Han, Ma, Li, Zheng, & Wang, ; Martínez, Marín, Gili, Penci, & Ribotta, ; Srikanlaya, Therdthai, Ritthiruangdej, & Zhou, ; Tan, Tan, & Easa, ; Wang et al, ). Hence, it is necessary to improve the process or develop a new formulation with additive ingredients in order to create adequate sensory and cooking qualities (Padalino, Conte, & Nobile, ).…”
Section: Introductionmentioning
confidence: 99%